Correction: Social Media Impact on the ‘Cosmos’ Blockchain Ecosystem: State and Prospect - Ivan Pavlyshyn; Anna Petrenko; Bohdan Opryshko; Bohdan Oliinyk; Sergii Kavun; Sergey Vasylchuk (Data Science Journal, 2024)
This article details a correction to: Pavlyshyn, I., Petrenko, A., Opryshko, B., Oliinyk, B., Kavun, S. 2024. Social Media Impact on the ‘Cosmos’ Blockchain Ecosystem: State and Prospect. Data Science Journal, 23(1): 8. DOI: https://doi.org/10.5334/dsj-2024-008